Planning Strategy on Natural and Cultural Tourist Attraction in Wana Village, East Lampung Regency - Desmala Sari; Evi Novianti; Aulia Iskandarsyah (Budapest International Research and Critics University, 2022)
Wana Village has a great deal of tourist attraction potential, including natural, cultural, historical, and culinary tourism and unique social life that includes more than one hundred classic traditional home architectures in the form of stilt houses typical of the Lampung tribe. In addition, there are ancient ceremonial customs, including the Melinting dance, which the village population frequently performs at various periods. In addition to ceremonies and arts, there are also traditional clothing and culinary specialties of Lampung Melinting that have attractiveness and cultural uniqueness that is still well maintained by the community so that they are still rich with the cultural values of the indigenous people of the Lampung tribe, making it a highly prospective area for tourist attraction development.This study seeks to identify the existing tourist attraction development strategies that enhance the growth of Wana's tourist attractions. This study employs a descriptive qualitative approach coupled with a SWOT analysis. The research site is in the East Lampung district village of Wana. The research findings indicate the significance of tourist attraction planning techniques that emphasize the planning of tourist attractions, accessibility, accommodation, amenities, and infrastructure supporting tourism activities..